Quantitative aspects of radon daughter exposure and lung cancer in underground miners. Issue 2 (May 1983) - Edling, C; Axelson, O
Abstract : Epidemiological studies have shown an excessive incidence of lung cancer in miners with exposure to radon daughters. The various risk estimates have ranged from six to 47 excess cases per 10(6) person years and working level month, but the effect of smoking has not been fully evaluated. The present study, among a group of iron ore miners, is an attempt to obtain quantitative information about the risk of lung cancer due to radon and its daughters among smoking and non-smoking miners. The results show a considerable risk for miners to develop lung cancer; even non-smoking miners seem to be at a rather high risk. An additive effect of smoking and exposure to radon daughters is indicated and an estimate of about 30-40 excess cases per 10(6) person years and working level month seems to apply on a life time basis to both smoking and non-smoking miners aged over 50.